Inspiring scientific wonder, curiosity and critical thinking in young minds: an interview with Audrey Dussutour (Communications Biology)
Audrey Dussutour is a Research Director at the National Center for Scientific Research (Toulouse, France), specializing in the adaptive behaviors of ants and slime molds. She has authored over 70 scientific papers and four award-winning science books. Dr. Dussutour has led two influential citizen science projects: “Raise Your Blob”, engaging 350,000 students, and “Behind the Blob”, mobilizing 15,000 volunteers to study climate change impact on slime molds. Her science communication efforts have been recognized with the National Order of Merit and the first CNRS Medal for scientific outreach. In this Q&A, she discusses the fascinating world of social insects and slime molds, the challenges of pursuing basic research outside mainstream funding priorities, and the importance of science education.